Analgesia in spinal surgery: morphine intrathecal versus erector plane block spinal - Selman B., Nicolás; Aguilera M, Germán; Maldonado C., Felipe (Boletín de Anestesia, 2022)
Spinal surgical procedures have increased in frequency in recent years.Perioperative pain management in this type of patient is essential, since it isdirectly related to surgical and rehabilitation outcomes. Although there aredifferent therapeutic strategies for adequate analgesic control, in this article wemade a synthesis based on the latest evidence on two particular techniques:intrathecal morphine and erector spinae plane block. We describe its mechanismsof action, benefits and adverse effects of each technique.